Հերոսի ճանապարհի մոնոմիֆի մոդելը Խաչատուր Աբովյանի «Վերք Հայաստանի» վեպում - Սողոյան, Աստղիկ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Структурное исследование романа Хачатура Абовяна «Раны Армении» позволяет проанализировать путешествие Агаси на основе мономифа пути героя, выдвинутого Дж. Кэмпбеллом. С этой точки зрения пространственные планы романа и действия персонажа приобретают важное функциональное значение. The structural study of Khachatur Abovyan’s novel “Wounds of Armenia” enables to analyze Aghasi’s voyage on the basis of the monomyth of hero’s journey, nominated by J. Campbell. From this point of view, the spatial plans of the novel and the hero’s steps gains important functional meaning.
Keywords: Armenian Literature